RADIOLOGICAL SCORING METHODS IN ANKYLOSING SPONDYLITIS: A COMPARISON OF THE RELIABILITY OF AVAILABLE METHODS - Ulusoy, Hasan; Kaya, Arzu; Kamanli, Ayhan; Akgol, Gurkan; Ozgocmen, Salih (Publisaude-Edicoes Medicas Lda, 2010)
Objective: To assess intra and inter-rater reliability of available radiological scoring methods in ankylosing spondylitis (AS). Patients and Methods: Two trained raters evaluated 44 complete sets of AS radiographs. The cervical and lumbar spine was graded from zero to 4 according to the Bath Ankylosing Spondylitis Radiology Index (BASRI). Hip joints were graded according to the BASRI-hip method. Sacroiliac (SI) joints were scored according to the New York method (0-4). The anterior and posterior sites of the lumbar spine were scored according to the Stoke Ankylosing Spondylitis Spinal Score (SASSS) method (0-72). Modified-SASSS was assessed by using the anterior sites of both the cervical and lumbar spine (0-72). Results: Both intra and inter-rater reliability were almost perfect for all the methods and intra-class correlation coefficient (ICC) for all the methods was relatively similar to each other. The BASRI-spine and BASRI-total showed intra and inter-rater ICC between 0.78 and 0.98. Both SASSS and modified-SASSS reached perfect intra and inter-rater reliability with ICC between 0.86 and 0.99. The ICC of the BASRI-hip was substantial to perfect, ranging from 0.77 to 0.88. Time spent to score a set of radiographs using the BASRI-spine was <45 seconds, whereas >60 seconds for both SASSS and mSASSS methods. Conclusion: After training, all of these methods have demonstrated almost perfect intra and inter-rater reliability. The BASRI was easier to perform and less time consuming than SASSS methods.
Keywords: Ankylosing Spondylitis; Radiological Scoring; BASRI; SASSS